DOES ENERGY CONSUMPTION FUEL ECONOMIC GROWTH IN INDIA? - Hrushikesh Mallick (Centre for Development Studies-WP388, 2007)
The paper examines whether energy use drives economic growth or vice versa in the Indian context during the period 1970-71 to 2004-05. Utilizing the Granger causality test, the study suggests that it is the economic growth that fuels more demand for both crude oil and electricity consumption and it is the only growth of coal consumptionthat drives economic growth. When influence of different components of energy on major two components of economic growth is investigated with the same causality test, none of the energy components found to be significantly influencing the two Components of economic growth viz. private consumption and private investment. In contrast, the out of sample forecasts in the variance decomposition analysis of Vector Autoregression (VAR) suggests that there could be a bi-directional influence betweenelectricity consumption and economic growth, other results remaining unchanged. Therefore, the study yields mixed and contradictory result as compared to the previous studies in the Indian context. However, on the basis of application of two econometric tools, the study with little more conviction could suggest for reducing crude oil and natural gas consumption at least in the consumption sectors which don't directlycontribute to production or add to the capital formation of the economy, for achieving higher rate of growth in the economy.